Analisis Optimalisasi Media Digital Dan Sumber Daya Manusia Dalam Meningkatkan Kinerja Lembaga Amil Zakat Sidogiri Cabang Bangkalan - Putri Maharani; Ahmad Makhtum (Universitas KH. Abdul Chalim Mojokerto, 2025)
The development of digital technology has had a significant impact on various sectors, including zakat management. The Amil Zakat Institution (LAZ) is required to be able to adapt to the use of digital media to expand reach, increase transparency, and strengthen community participation. In addition, the role of competent and professional human resources is able to manage effectively. LAZ Sidogiri Bangkalan Branch as one of the zakat institutions in the region has challenges in improving institutional performance through the use of technology and strengthening the quality of human resources. The purpose of this research is to find out the optimization of digital media and human resources can improve the performance of the amil zakat sidogiri institution of the bangkalan branch. This research method uses a qualitative method with a descriptive approach. Data sources consist of primary and secondary, primary data in the form of information from observation activities with observation and interview techniques. Meanwhile, secondary data is in the form of literature studies such as books, scientific journals, the internet as well as previous research and literature related to the research object. The Amil Zakat Sidogiri Bangkalan Branch has made optimal use of digital media as a means to increase effectiveness, efficiency, and transparency in the management of zakat, infaq, and alms. Human Resources in improving the performance of the Amil Zakat Sidogiri Bangkalan Branch shows that the implementation of Human Resources management at LAZ Sidogiri Bangkalan Branch has been carried out through four main management functions, namely planning, organizing, directing, and controlling running quite well.